2022
DOI: 10.1007/s00262-022-03161-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of characteristics and tumor targeting properties of extracellular vesicles derived from primary NK cells or NK-cell lines stimulated with IL-15 or IL-12/15/18

Abstract: NK cell-based therapies have shown promise for hematological cancer forms, but their use against solid tumors is hampered by their poor ability to infiltrate the tumor. NK cells release extracellular vesicles (EVs) containing cytolytic proteins, indicating that NK-cell derived EVs may have therapeutic potential. In this study, we compared the tumor-targeting potential of EVs derived from either primary NK cells or the NK cell lines NK-92 and KHYG-1 cultured in IL-15 alone or in combination with IL-12 and IL-18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 39 publications
0
45
0
1
Order By: Relevance
“…Fraction 7 were enriched for EVs with more translucent EVs, indicating a separate subpopulation of EVs. We previously reported enrichment of CD63, CD81, granzyme B and perforin in fraction 4 of SEC-separated EVs ( 14 ). TEM analysis demonstrated similar morphology of vesicles separated by SEC ( Figure 1G ).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Fraction 7 were enriched for EVs with more translucent EVs, indicating a separate subpopulation of EVs. We previously reported enrichment of CD63, CD81, granzyme B and perforin in fraction 4 of SEC-separated EVs ( 14 ). TEM analysis demonstrated similar morphology of vesicles separated by SEC ( Figure 1G ).…”
Section: Resultsmentioning
confidence: 98%
“…Furthermore, the microvesicle/ectosome marker CD99 ( 22 ), was exclusively detected in DG-UC fraction 5 with our mass spectrometry analysis, further confirming the enrichment of microvesicles within this fraction. Interestingly, we previously showed that the NK cell line KHYG-1 predominantly released EVs containing CD81 and not CD63, and that these vesicles contained low amounts of cytolytic proteins and lacked in killing activity towards tumor targets ( 14 ). These findings support the view that CD81 is present on two distinct vesicle subtypes, where CD81 + EVs may derive mainly from the plasma membrane, whereas a distinct population of CD81 + CD63 + vesicles is predominantly endosomally derived.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…peripheral blood and umbilical cord blood). Interestingly, a recent report revealed that extracellular vesicles derived from IL-12/15/18-stimulated NK-92 cells showed higher ability to induce apoptosis in HCT116 colon cancer cell spheroids in comparison with IL-15-stimulated controls ( 86 ). These results suggests that NK-92 cells are somehow sensitive to IL-12/15/18 stimulation and thus it would be interesting to explore if memory-like behavior could be imprinted in NK cell lines.…”
Section: Discussionmentioning
confidence: 99%